2019
DOI: 10.1038/s41598-019-51508-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel submerged Rotala rotundifolia, its growth characteristics and remediation potential for eutrophic waters

Abstract: The vegetative growth and remediation potential of Rotala rotundifolia, a novel submerged aquatic plant, for eutrophic waters were investigated on different sediments, and under a range of nitrogen concentrations. Rotala Rotundifolia grew better on silt than on sand and gravel in terms of plant height, tiller number and biomass accumulation. Percent increment of biomass was enhanced at low water nitrogen (ammonium nitrogen concentration ≤10 mg/L). The maximum total nitrogen and total phosphorus removals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results showed that there was a significant difference found between the comet goldfish reared with and without aquatic plants. The plants which supported highest SOD value of the fish were C. furcata is containing bioactive phytochemical such as saponin (Khalid et al, 2013;Subramoni et al, 2019) and Rotala can be used to effectively remove nitrogen and phosphorus in eutrophic waters (Gu et al, 2019). This study showed that the increased of total erythrocytes in different aquatic plant applications comet goldfish did not experience metabolic stress, which means that the aquatic plants have good performance in maintaining the fish health without damaging the blood vessels of the fish.…”
Section: Discussionmentioning
confidence: 71%
“…The results showed that there was a significant difference found between the comet goldfish reared with and without aquatic plants. The plants which supported highest SOD value of the fish were C. furcata is containing bioactive phytochemical such as saponin (Khalid et al, 2013;Subramoni et al, 2019) and Rotala can be used to effectively remove nitrogen and phosphorus in eutrophic waters (Gu et al, 2019). This study showed that the increased of total erythrocytes in different aquatic plant applications comet goldfish did not experience metabolic stress, which means that the aquatic plants have good performance in maintaining the fish health without damaging the blood vessels of the fish.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, organisms can be installed or manipulated at the edge of the habitat afflicted with toxic cyanobacteria (or in a connected habitat that is upstream) to modify environmental conditions. Examples of this include the planting of cover crops to reduce soil erosion in agricultural systems [49], the construction of riparian buffer zones and floating wetlands to curb or counteract influx of nutrients and cyanobacteria from terrestrial sources [49,50], and the seeding of lake habitats or adjacent riparian buffer zones with organisms capable of diverting, eliminating, or mineralizing nutrients (e.g., submerged aquatic vegetation and filter-feeding bivalves [51,52]).…”
Section: Control Methodsmentioning
confidence: 99%
“…Aquatic plants are broadly defined as plants that undergo chloroxygenic photosynthesis, containing numerous single-cell and multicellular species with abundant populations [20]. They play ecological and functional roles in various aspects, such as assimilating excessive nutrients (e.g., nitrogen and phosphorus) in eutrophic waters [21,22], removing heavy metals and nanoparticles in wastewater [23][24][25][26][27], and maintaining mutual benefit with aquatic animals [28], as well as future biofuels [29] and medicinal plants [30][31][32][33]. Importantly, most of them were beautiful ornamental plants in the aquarium, with high commercial value [2][3][4]34,35].…”
Section: Introductionmentioning
confidence: 99%